Organizational Citizenship Behaviours - Antecedents, Outcomes & Paradoxes: A Literature Review - Verghese, Aniisu (Ushus Journal of Business Management, 2020)
Organizational Citizenship Behaviours(OCBs) have a significant impact on how employees go over and beyond at the workplace and form a competitive edge for their firms. Grounded in industrial-organizational psychology, OCBs provide insights for leaders and managers to align and engage staff to improve organizational effectiveness. While a lot of studies have focused on the benefits of citizenship behaviours, there are paradoxes which need more attention. This paper reviews the literature on OCBs, the antecedents, outcomes and paradoxes when excessive OCBs can come in the way of organizational success.